EVALUASI KESESUAIAN PSAK 108 AKUNTANSI TRANSAKSI ASURANSI SYARIAH DENGAN MENGACU KEPADA ALQURAN DAN HADIST - Meiliana, Reva (Jurnal Manajemen Magister Darmajaya, 2015)
The objective of this research is to analysis and to evaluate PSAK 108 of accounting transaction shariâa insurance refer to Alquran and hadith it has not accordance with Islamic shariâa refer to Alquran and hadith. Source of data in this research is the PSAK 108 of accounting transaction shariâa insurance which will be evaluating the suitability with Islamic shariâa refer to Alquran and hadith.. The analyze data method is qualitative analysis by comparing as well as evaluating the suitability between the PSAK 108 of accounting transaction shariâa insurance with Islamic shariâa refer to Alquran and hadith. The results of this study indicate that there are still some aspects that require reevaluation about the conceps of shariâa insurance that suitable with Alquran and hadith, and the using akad in shariâa insurance that not suitable with Alquran and hadith. This study also gives recommendations to National Islamic Council as a representative ulama in Indonesia to reevaluate the fatwa that hooked with shariâa insuranceKeywords: PSAK 108, Accounting Transaction ShariâA Insurance